Doctor Tatiana V. Egorova – in memoriam - Żukowski, Waldemar (Biodiversity: Research and Conservation, 2007)
Tatiana Vladimirovna Egorova (1.12.1930-6.05.2007), doctor of biological sciences n a member of the NBiodiversity: Research and Conservationi Editorial Board n died in St. Petersburg. She was an eminent botanist, a specialist in the systematics of vascular plants, with a special interest in the family Cyperaceae and also Juncaceae and Liliaceae, as well as an outstanding expert in the rules of botanical nomenclature.